Inside Cover: Toward Hyperpolarized 19F Molecular Imaging via Reversible Exchange with Parahydrogen (ChemPhysChem 15/2017). Issue 15 (31st July 2017) - Shchepin, Roman V.; Goodson, Boyd M.; Theis, Thomas; Warren, Warren S.; Chekmenev, Eduard Y.
Abstract : The Inside Cover picture visualizes the chemistry and spin physics endowing spontaneous polarization transfer from parahydrogen gas to 19 F nuclear spins using reversible exchange of parahydrogen and to‐be‐hyperpolarized 19 F‐containing substrates on Iridium hexacoordinate complex. More information can be found in the Communication by E. Y. Chekmenev and co‐workers onpage 1961 in Issue 15, 2017 (DOI:10.1002/cphc.201700594 ).